COVID-19 shed light on Virchow's law of thrombosis - Hubert Daisley; Oneka Acco; Martina Daisley; Dennecia George; Lilly Paul; Arlene Rampersad; Johann Daisley (University of São Paulo, 2024)
Virchow's law of thrombosis states that thrombosis in a vessel occurs as a combination of the following: (i) injury to the vessel wall, (ii) stasis of blood flow, and (iii) blood hypercoagulability. Injury to the wall includes infection/inflammation and/or injury to the resident cells of the wall. We postulate that in COVID-19, the SARS-CoV-2 virus directly infects the alveolar type II cell or directly or indirectly infects/injures the pericyte, promoting inflammation and interaction with endothelial cells, thereby causing a cascade of events leading to our observation that thrombosis occurred within the walls of the pulmonary vessels and not in the lumen of the vascular circulation.